A case for seaweed aquaculture inclusion in U.S. nutrient pollution management. (July 2021) - Racine, Phoebe; Marley, AnnaClaire; Froehlich, Halley E.; Gaines, Steven D.; Ladner, Ian; MacAdam-Somer, Ilan; Bradley, Darcy
Abstract: Seaweed aquaculture is capable of removing large quantities of nitrogen and phosphorus from coastal ecosystems, yet seaweed has gained little traction for its potential role in targeted nutrient assimilation. Marine nutrient pollution is increasing around the world, contributing to expanding eutrophic conditions and co-occurring with other stressors that impact the state and stability of aquatic ecosystems. In the United States, climate change, legacy nitrogen, and nonpoint source pollution make it increasingly difficult to curb growing eutrophication and the associated effects, such as hypoxia (dissolved oxygen < 2 mgL -1 ). Employing a synthetic semi-quantitative approach, we use the Gulf of Mexico as a case study – a U.S. priority area for aquaculture with substantial nutrient pollution and one of the largest hypoxic zones on the planet – to assess the potential for native seaweed aquaculture to augment upstream pollution control with downstream nutrient assimilation. Results from this analysis suggest that given growing market demand, new product pathways, and nutrient pollution markets, seaweed aquaculture may be a feasible tool for nutrient assimilation that could subsidize, if not pay for itself.